Effects of Er: YAG, 980 nm and 810 nm Diode Lasers Irradiation on Biocompatibility of SLA Titanium Disks Using SaOs2 Cells Morphology - Birang, Reza; Tavakoli, Mehrnoosh; Birang, Ehsan (Journal of Dental School, 2018)
Objectives The use of lasers for the treatment of periimplant hard and soft tissues is now refmore than ever before. Achieving bone integrity. The aim of this study is to evaluate the effects of Er:YAG, 980 nm and 810 nm diode lasers irradiation on biocompatibility of SLA titanium disks by SaOs2 cells morphology. Methods In this in-vitro study sixty sterile titanium disks with SLA surface were divided into four equal subgroups. One subgroup was used as a control group and the remaining three groups were irradiated with Er:YAG laser 980nm and 810nm Doide lasers, separately. After laser irradiation, all discs were autoclaved at 121° C and placed in 24 appropriate plates. The SaOs2 cells were, then, added to the plates at a density of 2×104. The cells were incubated in DMEM, CO2, and penicillin-streptomycin medium at 37 ° C for 3 days. Then, the samples were extracted from the culture medium for scanning electron microscopy. Finally, the photograph was taken by SEM at magnifications of 750, 1000, 3000, and 5000. The analyses were performed through Kruskal-Wallis and Mann-Whitney tests. Results All three groups, irradiated by laser, and the control group have shown spreading cells with plentiful phylopodia, which means the morphology of a mature bone cell. The numbers were 20.7% (Er:YAG), 52.7% (980nm Diode), 48.8% (810nm Diode) and 38.7% (Control) groups, respectively, which were not statistically significant. Conclusion Er:YAG, 980nm and 810nm diode laser irradiations with the parameters mentioned in this study do not have any negative effects on osteoblast cells attachment and their maturity on titanium implants.